Житла роменського городища Водяне - Колода, В.В. (Археологія, 2015)
Статтю присвячено аналізу жител роменського періоду існування городища Водяне (Х — початок ХI ст.) у Харківській обл. Analyzed in the article, are the dwellings studied at Vodiane hill-fort, Zmiyiv Region in Kharkiv Oblast, representing Romny culture period of the site’s existence: from the 10th to the beginning of the 11th century.
On the whole, almost all diversity of house-building and interior variants peculiar to the Siverians’ (Romny culture) sites at the Siverskyi Donets River region are represented here. This is one of the features of Vodiane site, as far as house-building at other sites of Romny area is rather «standardized». The possible reason for such a variety is that Vodiane was located at south-eastern boundary of the Eastern Slavonic world within the zone that contacted with the Khazar population. Settling this area was rather risky venture for the Slavs. That’s why it can hardly be spoken of a planned or organized migration of an integral clan community. It is more likely that there were natives of different Romny communities who later comprised a neighbour’s community of Vodiane hill-fort.
The area of dwelling pits in fact never coincide with usable living space, which was appropriate for a small family of 4—6 members. The fact that the dwellings were synchronous and situated in pairs may evidence for kindred relations between their habitants within a single extended (enlarging) family. В статье анализируются жилища, исследованные на городище Водяное (Змиевской р-н Харьковской обл.), которые отражают роменский период существования памятника (Х — начало ХI вв.).
В целом здесь представлено практически все разнообразие вариантов жилищного домостроительства и интерьера, свойственного северянским (роменским) памятникам Северского Донца. В этом заключается одна из особенностей городища Водяное, так как на иных памятниках роменского ареала домостроительство более «стандартизировано». Возможные причины такого разнообразия заключаются в том, что городище Водяное располагалось на юго-восточных рубежах восточнославянского мира в пределах контактной зоны с населением Хазарии. Заселение этого края было для славян весьма рискованным предприятием. Поэтому в данном случае вряд ли можно говорить о планомерном или организованном переселении сюда какой-то цельной родовой общины. Скорее всего, это были выходцы из различных родовых роменских общин, составивших, впоследствии уже соседскую общину городища Водяное.
Площадь котлованов жилищ практически никогда не совпадает с полезной жилой площадью, которая была рассчитана на малую семью в 4—6 человек. Наличие практически синхронных, попарно расположенных жилищ может свидетельствовать о родственных отношениях между их жильцами в рамках одной большой (увеличившейся) семьи.